Question
upstudy study bank question image url

Suppose experimental data are represented by a set of points in the plane. An interpolating polynomial for the data is a polynomial whose graph passes through every point. In scientific work, such a polynomial can be used, for example, to estimate values between the known data points. Another use is to create curves for graphical images on a computer screen. One method for finding an interpolating polynomial is to solve a system of linear equations. Find the interpolating polynomial \( p(t)=a_{0}+a_{1} t+a_{2} t^{2} \) for the data \( (1,11),(2,19),(3,23) \). That is, find \( a_{0}, a_{1} \), and \( a_{2} \) such that the following is true. \[ \begin{array}{l} a_{0}+a_{1}(1)+a_{2}(1)^{2}=11 \\ a_{0}+a_{1}(2)+a_{2}(2)^{2}=19 \\ a_{0}+a_{1}(3)+a_{2}(3)^{2}=23 \end{array} \] Select the correct choice below and, if necessary, fill in the answer box to complete your choice. A. The interpolating polynomial is \( p(t)= \) \( \square \) . B. There are infinitely many possible interpolating polynomials. C. There does not exist an interpolating polynomial for the given data.

Ask by Chandler Huang. in the United States
Jan 30,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The interpolating polynomial is \( p(t) = -1 + 14t - 2t^{2} \).

Solution

To find the interpolating polynomial \( p(t) = a_{0} + a_{1}t + a_{2}t^{2} \) for the given data points \((1,11)\), \((2,19)\), and \((3,23)\), we need to solve the system of linear equations: \[ \begin{array}{l} a_{0} + a_{1}(1) + a_{2}(1)^{2} = 11 \\ a_{0} + a_{1}(2) + a_{2}(2)^{2} = 19 \\ a_{0} + a_{1}(3) + a_{2}(3)^{2} = 23 \end{array} \] Let's solve this system of linear equations to find the values of \( a_{0} \), \( a_{1} \), and \( a_{2} \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}a_{0}+a_{1}\times 1+a_{2}\times 1^{2}=11\\a_{0}+a_{1}\times 2+a_{2}\times 2^{2}=19\\a_{0}+a_{1}\times 3+a_{2}\times 3^{2}=23\end{array}\right.\) - step1: Calculate: \(\left\{ \begin{array}{l}a_{0}+a_{1}+a_{2}=11\\a_{0}+2a_{1}+4a_{2}=19\\a_{0}+3a_{1}+9a_{2}=23\end{array}\right.\) - step2: Solve the equation: \(\left\{ \begin{array}{l}a_{0}=11-a_{1}-a_{2}\\a_{0}+2a_{1}+4a_{2}=19\\a_{0}+3a_{1}+9a_{2}=23\end{array}\right.\) - step3: Substitute the value of \(a_{0}:\) \(\left\{ \begin{array}{l}11-a_{1}-a_{2}+2a_{1}+4a_{2}=19\\11-a_{1}-a_{2}+3a_{1}+9a_{2}=23\end{array}\right.\) - step4: Simplify: \(\left\{ \begin{array}{l}11+a_{1}+3a_{2}=19\\11+2a_{1}+8a_{2}=23\end{array}\right.\) - step5: Solve the equation: \(\left\{ \begin{array}{l}a_{1}=8-3a_{2}\\11+2a_{1}+8a_{2}=23\end{array}\right.\) - step6: Substitute the value of \(a_{1}:\) \(11+2\left(8-3a_{2}\right)+8a_{2}=23\) - step7: Simplify: \(27+2a_{2}=23\) - step8: Move the constant to the right side: \(2a_{2}=23-27\) - step9: Subtract the numbers: \(2a_{2}=-4\) - step10: Divide both sides: \(\frac{2a_{2}}{2}=\frac{-4}{2}\) - step11: Divide the numbers: \(a_{2}=-2\) - step12: Substitute the value of \(a_{2}:\) \(a_{1}=8-3\left(-2\right)\) - step13: Simplify: \(a_{1}=14\) - step14: Substitute the values of \(a_{1},a_{2}:\) \(a_{0}=11-14-\left(-2\right)\) - step15: Simplify: \(a_{0}=-1\) - step16: Calculate: \(\left\{ \begin{array}{l}a_{0}=-1\\a_{1}=14\\a_{2}=-2\end{array}\right.\) - step17: Check the solution: \(\left\{ \begin{array}{l}a_{0}=-1\\a_{1}=14\\a_{2}=-2\end{array}\right.\) - step18: Rewrite: \(\left(a_{0},a_{1},a_{2}\right) = \left(-1,14,-2\right)\) The solution to the system of linear equations is \( a_{0} = -1 \), \( a_{1} = 14 \), and \( a_{2} = -2 \). Therefore, the interpolating polynomial is \( p(t) = -1 + 14t - 2t^{2} \). So, the correct choice is: A. The interpolating polynomial is \( p(t) = -1 + 14t - 2t^{2} \).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Extra Insights

To find the interpolating polynomial \( p(t) = a_{0} + a_{1} t + a_{2} t^{2} \), we need to solve the given system of equations: 1. \( a_{0} + a_{1} \cdot 1 + a_{2} \cdot 1^2 = 11 \) 2. \( a_{0} + a_{1} \cdot 2 + a_{2} \cdot 2^2 = 19 \) 3. \( a_{0} + a_{1} \cdot 3 + a_{2} \cdot 3^2 = 23 \) This translates to: 1. \( a_{0} + a_{1} + a_{2} = 11 \) 2. \( a_{0} + 2a_{1} + 4a_{2} = 19 \) 3. \( a_{0} + 3a_{1} + 9a_{2} = 23 \) Next, we can eliminate \( a_{0} \) from these equations. Subtract equation 1 from equations 2 and 3: From equations (2 - 1): \[ (2a_{1} + 4a_{2}) - (a_{1} + a_{2}) = 19 - 11 \] \[ a_{1} + 3a_{2} = 8 \] → (4) From equations (3 - 1): \[ (3a_{1} + 9a_{2}) - (a_{1} + a_{2}) = 23 - 11 \] \[ 2a_{1} + 8a_{2} = 12 \] Dividing this equation by 2: \[ a_{1} + 4a_{2} = 6 \] → (5) Now we have: 1. \( a_{1} + 3a_{2} = 8 \) (equation 4) 2. \( a_{1} + 4a_{2} = 6 \) (equation 5) Subtract equation 4 from equation 5: \[ (a_{1} + 4a_{2}) - (a_{1} + 3a_{2}) = 6 - 8 \] \[ a_{2} = -2 \] Now substitute \( a_{2} \) back into equation 4: \[ a_{1} + 3(-2) = 8 \] \[ a_{1} - 6 = 8 \] \[ a_{1} = 14 \] Now substitute \( a_{1} \) and \( a_{2} \) back into equation 1 to find \( a_{0} \): \[ a_{0} + 14 - 2 = 11 \] \[ a_{0} + 12 = 11 \] \[ a_{0} = -1 \] Thus, we have: - \( a_{0} = -1 \) - \( a_{1} = 14 \) - \( a_{2} = -2 \) The interpolating polynomial is: \[ p(t) = -1 + 14t - 2t^{2} \] So, the correct choice is: A. The interpolating polynomial is \( p(t) = -2t^2 + 14t - 1 \).

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy